Transvaginal hysterotomy: A novel approach for the treatment of cesarean scar pregnancy - Zhenbo OuYang; Yujing Xu; Hongwei Li; Biting Zhong; Qiushi Zhang (Elsevier, 2019)
The objective of this study was to determine the outcome of using transvaginal hysterotomy as the first-line treatment of cesarean scar pregnancy (CSP). A literature review was performed on all eligible reports using this modality as the first-line treatment of CSP in English report. Relevant publications were obtained from the PubMed electronic database from inception to October 2018. Two hundred and fifteen cases reported in 7 articles were reviewed. The success rate of treatment was 99.5% (214/215), complication rate was 1.4% (3/215), and hysterectomy rate was 0.5% (1/215). Transvaginal hysterotomy could be considered as a good first-line treatment modality for CSP. Keywords: Cesarean scar pregnancy, Transvaginal resection, Hysterotomy